INTERACTIVE WORDWALL GAME MEDIA IN SCIENCE LEARNING FOR GRADE V ELEMENTARY SCHOOL - Sugiarti, Diyar; Widaty, Cucu (LPPM IKIP PGRI Pontianak, 2024)
This research was conducted with the aims to: (1) develop interactive learning media for science lessons for grade V elementary schools, (2) evaluate the relevance of using interactive learning media in science lessons in grade V elementary schools, (3) describe students' interest in online game-based Wordwall media in thematic learning of science content in grade V elementary schools. The research used the ADDIE method which has five research stages, namely analysis, design, development, implementation, and evaluation. Initial product development consists of media expert validation and material expert validation. The result is that the development of Wordwall media at the user stage obtained very good results.